PENGARUH GOAL SETTING TERHADAP PERFORMANCE : TINJAUAN TEORITIS - Ginting, Surya Dharma; Ariani, D. Wahyu (KINERJA, 2004)
This article is the conceptual view of goal setting theory and effects of goal setting on individual performance. Goal setting is recognized, and is a major theory of work motivation. Difficult goals have consistently been shown to lead to higher levels of performance than easy goals. If there is no commitment, a goal can have no motivational effect. Goals are central to current treatments of work motivation, and goal commitment is a necessary condition for difficult goals to result in higher task performance.Keywords : goals, goal-setting theory, performance